Delays in the Autism Spectrum Disorder Diagnostic Pathway: An Audit of Wait Times for Initial Assessment and Post-Diagnosis Support in Greater Preston - Cydney Tripley; Maria Hall (BJPsych Open)
Aims: Timely initiation of assessment for Autism Spectrum Disorder (ASD) is crucial as delays can significantly impact development of children and family well-being. This audit aimed to assess the adherence to National Institute for Health and Care Excellence (NICE) guideline recommendations of timely initiation of ASD assessment and follow-up care in the Greater Preston Area.